(3GdEbJUGO GdSjGSj (B/s - (3SGbhQ, YHO Gddgs ((3GdLRGFQ(B: s (3OGQ GdYdhe(B, s, 2004)
(3jVe CgejI GdJMdjd GdEbJUGOj , CSGdjH GdEfJGL GdELJeGYjI , eOGQS GdJMdjd GdEbJUGOjs
(3GdeQGLY U(B.140s
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdSjGSjs; (3GdJMdjd GdEbJUGOjs